The Implementation of Independent Learning Using E-Modul: Case Study of Students of Package C in SPNF SKB Pariaman City - Asna Fauziah; Jamaris Jamaris (Universitas Negeri Padang, 2022)
This research is motivated by the successful implementation of an independent learning program carried out on residents of learning equivalence package C, where the implementation of independent learning this time uses E-Modules as teaching materials, where the E-module teaching materials are formed with an attractive design so as to make E-module users -modules become interested in following the learning. The researcher's observations took place at SPNF SKB Pariaman City. This research uses a qualitative approach with a case study method, the researchers interviewed some of the learning residents who could be used as research subjects. The results of the study indicate that the results or evaluation of the implementation of independent learning using the E-Module are clearly seen from the final results or the results of the report cards of learning residents which can be said to be very satisfying, even though it is independent learning that is carried out alone at home. Keywords: Independent learning using E-Modules